The Water Needs of Grapevines in Central Poland - Barbara Jagosz; Stanisław Rolbiecki; Roman Rolbiecki; Ariel Łangowski; Hicran A. Sadan; Wiesław Ptach; Piotr Stachowski; Wiesława Kasperska-Wołowicz; Ferenc Pal-Fam; Daniel Liberacki (Agronomy, 2021)
Climate warming increases the water needs of plants. The aim of this study was to estimate the water needs of grapevines in central Poland. Water needs were calculated using the crop coefficients method. Reference evapotranspiration was assessed by the Blaney–Criddle’s equation, modified for climate conditions in Poland. Crop coefficients were assumed according to the Doorenbos and Pruitt method. Water needs were calculated using the data from four meteorological stations. Rainfall deficit with the probability occurrence of normal years, medium dry years, and very dry years was determined by the Ostromęcki’s method. Water needs of grapevines during the average growing season were estimated at 438 mm. Upward time trend in the water needs both in the period of May–October and June–August was estimated. Temporal variability in the water needs was significant for all of the provinces. These changes were mainly impacted by a significant increasing tendency in mean air temperature and less by precipitation totals that did not show a clear changing tendency. Due to climate change, vineyards will require irrigation in the near future. The use of resource-efficient irrigation requires a precise estimate of the grapevines’ water needs. The study identified the water requirements for grapevines in central Poland.